O USO DAS TECNOLOGIAS DA INFORMAÇÃO NA LIBERAÇÃO DE DADOS NA REDE: O CASO WIKILEAKS - Antunes, Bruno Conrado Demartini (2013)
This paper presents a case study of the Wikileaks website, founded by the former Australian hacker Julian Assange, who gained worldwide notoriety in 2010 by leaking secret United States Government documents regarding the wars in Afghanistan and Iraq, as well as from American embassies throughout the World. The publication of all of this content has generated great controversy in the high ranks of international politics and has shed a light on how the owners of power and monopolized media act to silence the discourses of certain narrators, discourses that can greatly jeopardize the political survival of these power actors. Thus, this work presents a case where new digital medias promoted what was portrayed as "the biggest leak in history" and how government actors reacted to this phenomena, with a campaign based on the pressure and defamation of Assange to try and cease all activities of website.